2016
DOI: 10.1103/physrevlett.117.075001
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Interaction of Edge-Localized Modes and Turbulent Eddies in Toroidal Plasma undern=1Magnetic Perturbation

Abstract: The effect of static n ¼ 1 resonant magnetic perturbation (RMP) on the spatial structure and temporal dynamics of edge-localized modes (ELMs) and edge turbulence in tokamak plasma has been investigated. Two-dimensional images measured by a millimeter-wave camera on the KSTAR tokamak revealed that the coherent filamentary modes (i.e., ELMs) are still present in the edge region when the usual large scale collapse of the edge confinement, i.e., the ELM crash, is completely suppressed by n ¼ 1 RMP. Cross-correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 30 publications
4
68
0
Order By: Relevance
“…This rotation braking likely induces the braking of the modes: edge modes are forced to be in phase with the penetrated mode induced by RMPs and thus to become static. The mode penetration inducing the sudden braking of the electron perpendicular velocity was observed in ELM suppression regimes in the experiments of DIII-D [29,30] and KSTAR [31,32]. The reduction below 1km/s of the velocity of saturated edge modes observed in non-bursting ELM suppression regimes of KSTAR [31,32], as well as the phase-locking of edge peeling-kink modes with static RMPs in grassy-ELM suppression regimes of DIII-D [33] is consistent with the edge mode locking found in this modeling.…”
Section: B Mechanism Of the Mode Braking During Elm Suppressionmentioning
confidence: 87%
“…This rotation braking likely induces the braking of the modes: edge modes are forced to be in phase with the penetrated mode induced by RMPs and thus to become static. The mode penetration inducing the sudden braking of the electron perpendicular velocity was observed in ELM suppression regimes in the experiments of DIII-D [29,30] and KSTAR [31,32]. The reduction below 1km/s of the velocity of saturated edge modes observed in non-bursting ELM suppression regimes of KSTAR [31,32], as well as the phase-locking of edge peeling-kink modes with static RMPs in grassy-ELM suppression regimes of DIII-D [33] is consistent with the edge mode locking found in this modeling.…”
Section: B Mechanism Of the Mode Braking During Elm Suppressionmentioning
confidence: 87%
“…For general information see [34][35][36][37] and for plasma-specific applications see, for example, [37,[42][43][44][45]. An early account of the application of higher order spectral techniques to plasma physics is given in [38].…”
Section: Appendix Amentioning
confidence: 99%
“…The bicoherence defined by equation (B.2) measures the strength of nonlinear wave coupling only, whereas equation (B.1) measures the strength of nonlinear energy flow. Bispectral analysis has been successfully applied to the MCI [23] and experimental plasma measurements [42][43][44], including those in the KSTAR tokamak [45].…”
Section: Appendix Amentioning
confidence: 99%
“…11 To study the dynamics of coupled modes P 1 and P 2 , we derived equations (12)-(13). We confirmed that the linear growth terms are crucial to determine the long-time behavior of P 1 and P 2 (Figs.5-6).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic perturbations have been used successfully to mitigate or suppress the crash [9][10][11] but the underlying mechanisms of mitigation and suppression are still unclear. Accordingly, it is crucial to understand the dynamics of ELM for more reliable and robust methods to avoid the crash.…”
Section: Introductionmentioning
confidence: 99%